The Use of Colors in Educational Programs on Visual Media and Its Impact on Attracting Students’ Attention towards it: Al-Iraqiya Educational Channel as a Model - Abduljabbar , Omer Jawad (Dirasat: Human and Social Sciences, 2023)
Objectives: This study seeks to explore how colors are employed in educational visual media, their impact on capturing students’ attention, the aesthetic values involved, color dimensions and categories, and the correlation between color usage and its influence on student attention. Methods: The study used the descriptive survey method, and data were obtained using the content analysis form tool to study (12) episodes of educational programs that are broadcast on the Al-Iraqiya Educational Channel through a questionnaire distributed among (100) students who watch Al-Iraqiya Educational Channel. The study used a simple random sample to collect information regarding the effect of the colors used in the programs in attracting their attention. Results: The study concluded that one of the most used color patterns in the educational programs of Al-Iraqiya Educational Channel is cold colors, the most color gradient is lighting, and the most color coordination is mono. It also showed that the extent of the effect of colors in the educational programs of Al-Iraqiya Educational Channel on attracting viewers’ attention towards them was of a high degree. There is also a correlation between the use of colors in educational programs that are broadcast and their effect on attracting the attention of students who watch them. Conclusions: The study observed a significant impact of colors in Al-Iraqiya Educational Channel’s programs on attracting students’ attention. It suggests training specialists in utilizing appropriate colors in educational designs and promoting awareness of color theories and research for optimal educational material design and audience engagement.